Ambient Backscatter Communications to Energize IoT Devices. Issue 2 (3rd March 2020) - Memon, Mudasar Latif; Saxena, Navrati; Roy, Abhishek; Singh, Sukhdeep; Shin, Dong Ryeol
Abstract : The expected rise of small devices in the Internet of Things (IoT) require these devices to operate without any power interruption. The replacement and recharging of batteries in these widely deployed small IoT devices is a challenging task. Recently, Ambient Backscatter Communications (AmB-Com) is introduced, which enables passive IoT devices to harvest power from nearby Radio Frequency (RF) signals. AmB-Com allows the passive devices to harvest energy and simultaneously transmit their information using the reflection of incident RF signals. This survey paper covers various types of ambient RF signals as the source of energy to energize passive IoT devices. Then, we show the utilization of multiple frequency bands to power up passive devices. In order to keep the balance between energy harvesting and information transfer, we discuss efficient power transfer schemes for AmB-Com in addition to energy management, resource allocation, and optimization techniques. Finally, we cover the performance of AmB-Com systems and highlight the research challenges in AmB-Com.